2022
DOI: 10.1101/2022.08.26.22279232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UB-612 Multitope Vaccine Targeting SARS-CoV-2 Spike and Non-Spike Proteins Provides Broad and Durable Immune Responses

Abstract: The SARS-CoV-2 non-Spike (S) structural protein targets of nucleocapsid (N), membrane (M) and envelope (E), critical in the host cell interferon response and memory T-cell immunity, have been grossly overlooked since the inception of COVID vaccine development. To pursue a universal (pan-sarbecovirus) vaccine against ever-emergent future mutants, we explored booster immunogenicity of UB-612, a multitope-vaccine that contains S1-RBD-sFc protein and sequence-conserved rationally designed promiscuous Th and CTL ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Investigation of the booster immunogenicity of UB-612 showed that UB-612 booster was safe and well tolerated without concerns of sevear adverse effects, and also it provided potent, broad, and long-lasting B-cell and T-cell memory immunity. Based on the results, the UB-612 booster induces high viral-neutralizing antibodies against Omicron BA.1/BA.2/and current BA.5 variants, offering a potential to be used as a universal vaccine to fend off Omicrons and new VOCs ( Guirakhoo et al, 2022a ; C.Y. Wang et al, 2022 ).…”
Section: Protein Subunit Vaccine Design For Covid-19mentioning
confidence: 99%
“…Investigation of the booster immunogenicity of UB-612 showed that UB-612 booster was safe and well tolerated without concerns of sevear adverse effects, and also it provided potent, broad, and long-lasting B-cell and T-cell memory immunity. Based on the results, the UB-612 booster induces high viral-neutralizing antibodies against Omicron BA.1/BA.2/and current BA.5 variants, offering a potential to be used as a universal vaccine to fend off Omicrons and new VOCs ( Guirakhoo et al, 2022a ; C.Y. Wang et al, 2022 ).…”
Section: Protein Subunit Vaccine Design For Covid-19mentioning
confidence: 99%